Stray Light Calibration and Correction of EnMAP's Imaging Spectrometers - Baumgartner, Andreas; Henning Kohler, Claas; Baur, Simon; Wachter, Richard; Polz, Leonhard; Serdyuchenko, Anna (IEEE transactions on geoscience and remote sensing, 2025)
We report on the on-ground stray light calibration of the hyperspectral Environmental Mapping and Analysis Program (EnMAP) satellite mission, which was successfully launched into space on April 1, 2022. EnMAP's optical payload consists of a visible and near-infrared (VNIR) (420-1000 nm) and a short wavelength infrared (SWIR) (900-2450 nm) imaging spectrometer. Using a custom-built light source and a collimator, we determined the diffuse stray light by measuring the point spread functions (PSFs) at 12 spatial and 15 (11 VNIR, 4 SWIR) spectral positions with a dynamic range between eight and nine orders of magnitude. Additionally, we measured the out-of-field stray light in along-track direction over an angular range of ±0.2°, resulting in an along-track response function (AltRF) for each spectrometer unit with a dynamic range of \sim 10^{7} . To reduce memory usage and computational time, we use a binned stray light extraction matrix to correct the diffuse stray light. The along-track out-of-field stray light of individual frames is corrected by subtracting preceding and following frames that are weighted with the AltRF. Finally, we show with simulations the impact of both types of stray light on a test scene and evaluate the performance of the presented correction methods in the same manner.